Central nervous system of Rhipicephalus sanguineus ticks (Acari: Ixodidae): an ultrastructural study - Roma, Gislaine Cristina [UNESP]; Nunes, Pablo Henrique; Oliveira, Patricia Rosa de [UNESP]; Remedio, Rafael Neodini [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Springer, 2012)
This study performed the ultrastructural description of the synganglion of Rhipicephalus sanguineus males and females, aiming to contribute to the understanding of the cellular organization of this organ. The results show that the central nervous system of these individuals consists of a mass of fused nerves, named synganglion, from where nerves emerge towards several parts of the body. It is surrounded by the neural lamella, a uniform and acellular layer, constituted by repeated layers of homogeneous and finely granular material. The perineurium is just below, composed of glial cells, which extensions invaginate throughout the nervous tissue. The synganglion is internally divided into an outer cortex, which contains the cellular bodies of the neural cells and an inner neuropile. The neural cells can be classified into two types according to cell size, cytoplasm-nucleus relation, and neurosecretory activity. Type I cells are oval or spherical and present a large nucleus occupying most part of the cytoplasm, which contains few organelles. Type 2 cells are polygonal, present a great cytoplasm volume, and their nuclei are located in the cell periphery. The cytoplasm of these cells contains a well-developed rough endoplasmic reticulum, Golgi regions, mitochondria, and several neurosecretory granules. The subperineurium and the tracheal ramifications are found between the cortex and the neuropile. The latter is formed mainly by neural fibers, tracheal elements, and glial cells. The results obtained show that R. sanguineus males' and females' nervous tissue present an ultrastructural organization similar to the one described in the literature for other tick species.